Investment Incentives as Tariff Substitutes: A Comprehensive Measure of Protection - Bond, Eric W.; Guisinger, Stephen E. (The Review of Economics and Statistics, 1985)
This paper extends the effective rate of protection measure to include the effect of investment incentives on resource allocation when capital is mobile internationally. This measure illustrates how investment incentives (such as capital grants and tax holidays) serve as another form of non-tariff barrier that may be substituted for tariffs in the protection package. Calculations made for the case of Ireland indicate that the substitution of investment incentives for tariffs after Ireland's entry into the EEC left the ranking of industries on the basis of effective protection to labor unaffected by the tariff cuts. R ECENT work on commercial policy has suggested that the pattern of tariff and non-tariff protection is the outcome of a political process, and reflects the profitability of protection to domestic producers and the costs of organizing producers.' In such an environment, reductions in tariff barriers negotiated outside the domestic political process (as in multilateral tariff reductions or entry into a free trade area) should result in political pressure by producers for the substitution of non-tariff barriers in the protection package. For example, Marvel and Ray (1983) argue that the Kennedy Round tariff cuts overstate the amount of trade liberalization that has occurred in the United States because of the erection of nontariff barriers that have partially reduced the effect of the tariff cuts. The purpose of this paper is to develop a comprehensive measure of protection, capturing the extent to which trade policies (tariffs and quotas) and investment incentives provide protection to domestic resources, and to present an illustration of the substitution of investment incentives for tariff protection following Ireland's entry into the Common Market. Investment incentives provide an alternative form of protection which may be important in countries where governments are constrained from altering tariffs, or where subsidies to export industries are limited by the likelihood of countervailing duties. Section I presents the rental cost of capital model, which can be used to combine the effects of various types of investment incentives (such as capital grants, tax holidays, and accelerated depreciation allowances) into a single measure that indicates the effect of these incentives on the cost of capital services to firms. This measure extends earlier work by Kopits (1975), Hufbauer (1975), and Guisinger and Kazi (1978), and can be used to make international comparisons of the level of investment incentives. Section II incorporates the rental cost of capital index into Corden's (1966) effective rate of protection measure when capital is mobile internationally. The resulting effective rate of protection to labor includes both output market distortions (tariffs and quotas) and factor market distortions for mobile factors (investment incentives). Therefore, reductions in tariff protection can be offset by increases in factor incentives to maintain the same effective rate of protection to labor in an industry.2 Section III provides a calculation of effective rates of protection to labor in eleven Irish manufacturing industries in 1966 and in 1977. Between these two years, tariff protection declined substantially following Ireland's accession to the Common Market. During the same interval, Ireland undertook a major reorganization of the Industrial Development Authority, armed with a wide array of fiscal incentives and charged with increasing industrial investment. We demonReceived for publication January 26, 1984. Revision accepted for publication July 5, 1984. *The Pennsylvania State University and University of Texas at Dallas, respectively. The authors wish to acknowledge useful comments from Malcolm Gillis, Ed Tower, Bee Roberts, and two anonymous referees on an earlier draft. We are particularly grateful to Dermott MacAleese, who provided us with unpublished data on protection in Ireland. The authors began work on this topic while serving as consultants to the International Finance Corporation. The views expressed .are not necessarily those of the World Bank or its affiliates. 1 Caves (1976) and Pincus (1975) find some support for the role of political pressure groups in tariff policy, and Ray (1981) broadens the analysis to include both tariff and non-tariff barriers. Takacs (1981) and Finger, Hall, and Nelson (1982) also find political variables important in escape clause and less than fair value cases. 2A recent study of the investment strategies of multinational corporations conducted for the World Bank (Guisinger (1983)) found that in the majority of cases examined, host country incentives were the determining factor in the location decision. The World Bank study defined incentives broadly to include both tariff protection and investment incentives, as our measure suggests. For previous work on the effect of tariffs on multinational location decisions see Horst (1972) and Orr (1975).